SUSTAINABILITY PROGRAM: TRANSITION AND IMPLEMENTATION IN A GREEN ECONOMY - Nathania Arindha Putri; Ramadhan Adin Nugroho; Hwihanus (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research entitled "Sustainability Program: Transition and Implementation in a Green Economy" aims to examine the transition to a green economy and its implementation through meta-analysis. A green economy is an economic model that aims to improve human well-being and social equality, while reducing environmental risks and ecological scarcity. In this research, the meta-analysis method was used to combine the results of various previous studies relevant to this topic. Data was collected from academic journals, government reports, and case studies from various countries. The meta-analysis results show that the transition to a green economy requires significant structural changes in policy, technology and societal behavior. Implementation of sustainability programs shows varying results depending on regional context, technological readiness, and supporting government policies. This research concludes that despite major challenges, the transition to a green economy is a crucial step to achieve sustainable development. This study provides policy recommendations to accelerate this transition, including strengthening environmental regulations, incentives for green innovation, and increasing public awareness of the importance of the green economy.